Ethical leadership and public accountability: Problematiques of South Africa’s State-Owned Enterprises - Kgobe, F. K. L.; Chauke, K. R. (Technium Social Sciences Journal, 2021)
This paper aims to explore the potency of ethical frameworks in the advent of a democratic dispensation in State-Owned Enterprises in an attempt to address conundrums of unethical leadership and devastating public accountability. This paper argues that South Africa is grappling with fitting in the notion of ethos and accountability. On the same line, the contestation about the impasse of the State-Owned Enterprises (SOEs) befits germane in the topical and constant political transformation in South Africa. SOEs endure eccentric to those serving it and those who benefit from it, leading to a lack of orthodoxy by public officials to ethical framework prescribed and contemplated in legislation for good conduct in public services. Ethical leadership and public accountability are two sides of the same coin; however, they serve as a nut and bolt of a well-functioning public administration. The two are inseparable. The paper is theoretical as such, and it is epistemologically juxtaposed and grounded or underpinned by agency theory and its ideals. Be that as it may, it further depends on literature base review for its premise, argument, crux, and purpose and drawing up results and conclusion. Thus, the paper gathers information regarding the various scholars’ notions on ethical leadership and public accountability from related articles, journals, and books. The paper reveals that the South African State-Owned Enterprises are antagonized and branded by unethical leaders and public accountability challenges. At this juncture, the SOEs are faced with poor fiscal coordination and management. The paper further reveals that the SOEs are swimming in the pool of debts. The conclusion that can be deduced from this paper is that it calls for strengthening and reforming all legislative prescripts that govern the State-Owned Enterprises. Public administrators must avoid incubating politicians as it creates the ground for corruption and various types of ethical dilemmas.